Kecepatan dan Presentase Infeksi Penyakit Ice-Ice pada Kappaphycus alvarezii di Perairan Bluto Sumenep [Velocity and Infection Percentage of Ice-Ice Disease on Kappaphycus alvarezii in Bluto Beach Sumenep] - Apri Arisandi; Marsoed Marsoed; Happy Nursyam; Aida Sartimbul (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract Seaweed is vulnerable to be infected by disease due to unlikely environmental circumstance. This condition could cause impact on the optimum growth of seaweed. This research was carried out to understand the rate and percentage of ice-ice disease on Kappaphycus alvarezii. Seven units of seaweed rafts were used. Each of them was observed every 12 hours. Results of this research indicated that the percentage of infection was relatively higher during the day on the observation units which were located next to the shore (1,008%). Three days after the infection of ice-ice disease occurred, the mortality of Kappaphycus alvarezii was certain. Therefore, it was recommended that harvesting Kappaphycus alvarezii should be done one day after the indications of ice-ice disease were noticed.